2008
DOI: 10.1161/strokeaha.107.495036
|View full text |Cite|
|
Sign up to set email alerts
|

Barriers to the Use of Anticoagulation for Nonvalvular Atrial Fibrillation

Abstract: Background and Purpose-Anticoagulation reduces the risk of stroke in nonvalvular atrial fibrillation yet remains underused. We explored barriers to the use of anticoagulants among Australian family physicians. Methods-The authors conducted a representative, national survey. Results-Of the 596 (64.4%) eligible family physicians who participated, 15.8% reported having a patient with nonvalvular atrial fibrillation experience an intracranial hemorrhage with anticoagulation and 45.8% had a patient with known nonva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 12 publications
2
75
0
1
Order By: Relevance
“…4,5 For Nonadherence to guideline-directed OAC use may also be influenced by many variables, including the healthcare system, physician factor, and patient-level considerations. 35 To improve OAC treatment among patients with AF, numerous methods have included establishment of specialized anticoagulation clinics, antithrombotic education programs, anticoagulation intensity monitoring, point-of-care patient self-testing, and computerized algorithms for warfarin dose adjustment. 36 In addition, promoting a rational appraisal of the risks and benefits of anticoagulation is essential to reduce decisional conflicts for physicians.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 For Nonadherence to guideline-directed OAC use may also be influenced by many variables, including the healthcare system, physician factor, and patient-level considerations. 35 To improve OAC treatment among patients with AF, numerous methods have included establishment of specialized anticoagulation clinics, antithrombotic education programs, anticoagulation intensity monitoring, point-of-care patient self-testing, and computerized algorithms for warfarin dose adjustment. 36 In addition, promoting a rational appraisal of the risks and benefits of anticoagulation is essential to reduce decisional conflicts for physicians.…”
Section: Discussionmentioning
confidence: 99%
“…9 Another local study reported more than 30% of AF patients did not receive appropriate antithrombotic therapy; 34% of AF patients were treated with aspirin alone, and 22% of them were not receiving any antithrombotic therapy. 10 The aims of this study were to assess the knowledge of Hong Kong physicians in stroke prevention management for AF patients and the understanding of AF and warfarin therapy in Hong Kong Chinese AF patients, and to compare the knowledge levels of both physicians and patients with those in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Although shared decision-making, patients' preferences, and noncompliance with medical regimens are certainly factors in OAC underuse, clinicians' judgment appears to play the chief role. [21][22][23][24] The reasons typically cited for not prescribing OACs are bleeding risk, older age, the risk of falls, and patient noncompliance. [23][24][25] In fact, two of the strongest risk factors for stroke in AF-prior stroke and increasing age-are actually indicators of withholding appropriate anticoagulant therapy.…”
Section: Underuse Of Oral Anticoagulants For Nonvalvular Atrial Fibrimentioning
confidence: 99%